2004
DOI: 10.1159/000082330
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Cedar-Pollen-Specific IL-5 Production in Infants with Atopic Dermatitis

Abstract: Background: Although food allergens and house dust mites are thought to contribute to the development of atopic dermatitis (AD) in infants, the influence of pollens has not yet been well defined. Objective: This study attempted to clarify the effect of Japanese cedar pollens (JCPs), which are scattered in Japan between February and April, on AD in infants. Methods: In the first study, seasonal changes in the number of patients who first visited our institute due to AD were analyzed by reviewing medical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Similar changes correlating to age are seen in JCP-induced IL-5 production, which also peaks in infants (<1 year) [25]. This pattern clearly differs than that of HDM-induced IL-5 production, which remains high even after the age of 1, similar to IL-4 production [13, 27].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Similar changes correlating to age are seen in JCP-induced IL-5 production, which also peaks in infants (<1 year) [25]. This pattern clearly differs than that of HDM-induced IL-5 production, which remains high even after the age of 1, similar to IL-4 production [13, 27].…”
Section: Discussionmentioning
confidence: 63%
“…Eosinophils and their products such as ECP are thought to play a critical role in the pathogenesis of AD [23, 24]. We previously reported that IL-5 production by PBMCs upon stimulation with HDM or Japanese cedar pollens (JCP) was already increased in infants with AD, despite a lack of IgE for these allergens in the serum [20, 25]. In the present study, we also demonstrated that stimulation of PBMCs with OVA induces a large amount of IL-5 production in infants (<1 year) with moderate to severe AD.…”
Section: Discussionmentioning
confidence: 99%
“…Eczema severity appeared to fall during the first 3 months of the trial but again there may be a seasonal effect with symptoms improving during what was for most children enrolled in the trial, the winter months at the start of the trial. Some studies report increased symptom severity associated with the release of pollen during spring (10) while others report worse symptoms in winter associated with low sun exposure and low temperature (11). A specific effect of Johrei on eczema is difficult to reconcile with the fact that several families dropped out at 3 months despite this apparent improvement.…”
Section: Discussionmentioning
confidence: 99%